Strategi Pemasaran Menggunakan Analisis Ansoff Dalam Meningkatkan Pemasaran Produk di Pegadaian Kantor Cabang Purwokerto - Zeliana, Aura Nadisha; Shafrani, Yoiz Shofwa; Saputri, Imel Nurul; Fernansyah, Nio Kenshi Pratama (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Pegadaian is one of the Islamic financial institutions in Indonesia that continues to expand its market share through various marketing strategies. This study aims to analyze the market penetration strategies implemented by Pegadaian and identify the efforts that can be made to increase customer interest. The research method used is descriptive qualitative with a literature study approach from various accredited national journals in the last five years, as well as document analysis related to Pegadaian marketing strategies. The results of this study reveal that Pegadaian market penetration strategy is carried out through the optimization of digital promotion, the development of innovative products and services, and the improvement of financial literacy in society. Digital promotion strategies are carried out by utilizing social media and other online platforms to increase product awareness and education to the general public. In addition, product development such as Arrum Haji and Tabungan Emas has become an effective innovation in meeting market needs. Pegadaian is also actively conducting financial education through seminars, workshops, and outreach programs as a form of improving financial literacy and customer loyalty. These three strategies have consistently proven to attract new customers, increase loyalty, and strengthen Pegadaian position amidst the competition in Islamic financial institutions. This research contributes to enriching the study of marketing strategies for Islamic financial institutions, particularly in the pawnshop sector. The novelty of this research lies in the systematic and detailed mapping of Pegadaian market penetration strategies based on the latest literature.